HUBUNGAN SIKAP, PERILAKU DAN PARTISIPASI KADER POSBINDU PTM TERHADAP KEPATUHAN PASIEN DALAM UPAYA PEMERIKSAAN PENYAKIT HIPERTENSI DI KECAMATAN KETOL - Ica Nabila; Maulina Iriyanti; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT Hypertension or also known as high blood pressure is a condition in which blood vessels continuously increase pressure. Blood is carried from the heart to all parts of the body through the blood vessels. Blood pressure is created from the pressure of blood pushing against the walls of blood vessels (arteries) as it is pumped by the heart. Research methodology: quantitative research using cross sectional method, as well as data collection carried out jointly by using questionnaires. The total population of 534 hypertensive patients and samples in this study amounted to 84 respondents, the independent variable in this study (attitude, behavior and cadre participation) the dependent variable (patient compliance in the examination of hypertension). Results: 0.000<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between the attitude of Posbindu PTM cadres to the compliance of hypertensive patients in the examination of hypertension in Ketol. Based on The Chi-Square test results obtained a significant value of 0.005<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between the behavior of Posbindu PTM cadres to the compliance of hypertensive patients in the examination of hypertension in Ketol. Based on The Chi-Square test results obtained a significant value of 0.002<0.05. So, Ha was accepted and Ho was rejected. It can be concluded that there is a significant relationship between the participation of Posbindu PTM cadres to the compliance of hypertensive patients in the examination of hypertension in Ketol. Initiation and suggestion: the response to the study of attitude variables negative category as much as 51 (60.7%) positive 33 (39.3%). Responses to behavioral variables positive category as much as 39 (46.4%) negative 45 (53.6.8%). Responses to the variable participation with the category "yes" as much as 36 (42.9%) category "No" 48 (57.1%). Suggestions that for health workers to increase direct participation, for researchers in the future in order to increase visits. Keywords : Attitude, Behavior, Participation, Compliance